Sustainable Material Selection in Construction using Multi Criteria Decision Analysis (MCDA) - Sudakova Anna; Lalitha Yaragudipati Sri; Reddy K. Ramakrishna; Kataria Ansh; Prakash Sunil; Sharma Gazal; Mittal Sachin; Kumar Yogesh; Almusawi Muntather (E3S Web of Conferences)
Sustainable material is an innovative combination of hybrid engineering methods and advanced Multi Criteria Decision that seeks to transform the properties of materials on different surfaces. This scientific inquiry uncovers the transformative framework of Sustainable material. In addition, the study uncovers transformation factors (TF) for the integration of nanomaterials (TF = 1.8), Multi Criteria Decision that resemble biological processes (TF = 2.5), deposition aided by plasma (TF = 1.6), and Multi Criteria Decision made using a sol-gel hybrid method (TF = 2.0). These results demonstrate significant enhancements via the use of substantial experimental data. Biomimicry Multi Criteria Decision surpass conventional Multi Criteria Decision in terms of adhesion strength (22 MPa), abrasion resistance (0.3 mm3), and corrosion protection (300 hours). This is shown by the remarkable improvements seen in coating performance metrics. Sustainable material's adaptability is shown via experiments into material transformation, enhancing surface hardness, hydrophobicity, transparency, and tensile strength over a diverse spectrum of substrates. Environmental resistance assessments emphasize the longevity of Multi Criteria Decision, whereas biomimicry Multi Criteria Decision demonstrate remarkable resistance to UV radiation (600 hours), thermal stability (350 degrees Celsius), and chemical resistance. The precise and comprehensive information provided by percentage change values highlights the distinctive characteristics of Sustainable material, establishing it as a disruptive presence in the world of material science and engineering. This work contributes to the continuing discourse on advanced materials and offers valuable insights that may be used to many sectors such as aeronautical engineering, biomedical engineering, and other related areas.